Pembiayaan Syariah di Bank Perkreditan Rakyat Syariah pada Masa Pandemi Covid-19 - Muthoifin, Muthoifin; Nurhayatii, Aisyah; Amrin, Amrin; Hambali, Ahmad Imam (Prosiding University Research Colloquium, 2022)
Globally, the COVID-19 pandemic has affected changing in the decline in the world economy, including the Islamic banking industry, but the performance of BPRS still shows a positive direction. Therefore, this study is interested in discussing the implementation of sharia compliance in murabahah contracts at BPRS Dana Amanah Surakarta murabahah which is one of the most widely applied types of contracts in Islamic banking financing activities and the impact of the pandemic on murabahah contracts. The purpose of this study is to examine sharia compliance in the implementation of murabahah contracts and the impact of the pandemic on murabahah contracts at BPRS Dana Amanah Surakarta. This research is a field research with an interpretive approach. Data analysis in this study uses content analysis which analyzes the main sources of research in the form of interview data and contract documents related to murabahah at BPRS Dana Amanah Surakarta. The conclusion is that there are two kinds of murabahah financing: Sindication and non sindication. And there aare two kinds of murabaha contracts, namely the murabahah bil wa'ad lil syira contract and the murabahah bi wakalah contract. In the murabahah bil wakalah contract, there are two schemes, the first is direct payment to the supplier and the second is payment through the customer's account. Sharia compliance in the murabahah contract is in accordance with sharia and the DSN-MUI fatwa, there is only a slight difference in the application of the second scheme of murabahah bil wakalah with the DSN-MUI fatwa.